An analytical study between banking risks and islamic financing formulas - SLIMANI, Salim (Journal of Human Sciences, 2025)
Through this research, we sought to analyze a portion of the study conducted by researchers Tariqullah Khan and Habib Ahmed (in their 2001 publication "Risk Management: Analysis of Issues in the Islamic Financial Industry" by the Islamic Development Bank's Islamic Research and Training Institute) using Principal Component Analysis (PCA) and Agglomerative Hierarchical Clustering (AHC) methodologies.Our analysis concluded that the murabaha formula represents the least risky financing structure among all examined instruments, followed by ijarah as the second least risk-intensive arrangement. Conversely, the musharakah formula emerged as the most risk-prone financing mechanism, followed by the diminishing musharakah formula as the second most risk-intensive structure.Regarding risk typology, liquidity risk was identified as the least significant risk factor across various financing formulas, followed by credit risk in terms of relative severity. Operational risk constituted the most critical risk dimension across different financing structures, followed by profit margin risk as the second most consequential vulnerability.